Hubungan Status Nutrisi Ibu Nifas Dengan Proses Penyembuhan Luka Post Operasi Sectio Caesarea Di RSUD Dr. Moewardi - NAESEE, NIAINU; , Winarsih Nur Ambarwati, S.Kep.Ns.ETN.M.Kep; , Dewi Suryandari, S.kep.Ns (2015)
Background. Childbirth is the last phase of the most important in the process of pregnancy. This period that many thrilling a woman who gave birth, also his partner. Therefore, labor is the culmination of all processes and efforts that have been done so that everything ended well, that his mother can give birth to her baby are healthy and perfect. Sectio caesarea generally is defined as the birth of the fetus through an incision in the abdominal wall (laparotomy) and uterus wall. Total operating sectio caesarea has increased in 30 years ago one of the 12 ends with a surgical delivery section caesarean now this ratio is 1 of 3 delivery. Research Purposes. To determine the relationship of postpartum maternal nutritional status on postoperative wound healing section caesarean in Dr Moewardi Hospital. Method. The design study is a quantitative research design used cross-secctional. The research sample of 68 people puerperal women, with accidental sampling technique using sample. Research instrument using IMT measurement tools and observation sheet with wound section caesarean and analyzed using chi-square. The Results. The results in this study are known nutritional status based on the normal nutritional status of 31 people (45.6%), based on the results of the chi-square test showed that there is a relationship between postpartum maternal nutritional status with the wound healing process post section caesarean in Dr Moewardi Hospital with the value x2 = 15.963, p = 0.001. Conclusion. Results of chi-square indicates p value 0.001 (<0.05), then Ho is rejected. So can be concluded this was no association between postpartum maternal nutritional status with the wound healing process post sectio caesarea in Dr Moewardi Hospital.